Fitoremediasi Logam Berat Pb dan Cu Pada Mangrove Rhizophora Apiculata dan Sonneratia Alba di Muara Sungai Badung Denpasar Bali - Karel Yesaya Mbaba (Universitas Hamzanwadi, 2024)
Increased activity in the Badung river basin has an impact on water quality, including river estuaries and the sea, which will affect the environmental ecosystem. One of the water and sediment pollutants is heavy metals. Heavy metal pollution can be overcome with phytoremediation. This research aims to analyze the ability of the Rhizophora apiculata and Sonneratia alba mangroves to accumulate the heavy metals Pb and Cu. Phytoremediation naturally occurs at river estuaries, namely in mangrove plants. Metal absorption in mangroves occurs in the roots which are then carried to the leaves. The research was conducted at the mouth of the Badung River, Denpasar, Bali. The research results show that the Pb metal content in water has exceeded the quality standards for marine tourism and marine biota based on PPRI No. 22 of 2021, namely an average of 0.005 mg/l. Metal absorption occurs in two types of mangroves, namely Rhizophora apiculata and Sonneratia alba. The highest metal absorption in mangroves is the Sonneratia alba species. Mangroves translocate metals from roots to leaves. From the research results, mangroves are classified as low accumulator plans.